2018
DOI: 10.1080/15623599.2018.1462443
|View full text |Cite
|
Sign up to set email alerts
|

Labour productivity statistics: a reality check for the Norwegian construction industry

Abstract: Construction is one of the largest sectors that drive the global economy, yet it has failed to receive the necessary attention from the policymakers and investors. The existing construction statistics report the declining state of labour productivity. However, existing statistics often fail to reflect the true scope and economic impact of construction. They mainly account for on-site construction activities, but overlook the manufacturing of construction products and services in construction labour productivit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 31 publications
0
14
0
Order By: Relevance
“…Additionally, the relative importance of HRM practices in the three project types is different because of the variations in project locations (countries). Similarly, Ahmad et al (2018) concluded that construction products and services vary from country to country.…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, the relative importance of HRM practices in the three project types is different because of the variations in project locations (countries). Similarly, Ahmad et al (2018) concluded that construction products and services vary from country to country.…”
Section: Resultsmentioning
confidence: 99%
“…It is also necessary to keep in mind the so-called "productivity paradox" (Dementyev, 2019) when the overall company productivity temporarily drops despite substantial investments into modernization of technologies and production lines. Altogether, implementation of productivity increase measures requires development of company programs of using the tools listed above that allow assessing their effectiveness and viability in the areas of goods and services production and consumption (Ahmad et al, 2020).…”
Section: Tools For Increasing Integral Productivitymentioning
confidence: 99%
“…This was identified by Howell in 1992 (Hackett et al 2019). As shown in Figure 1, while all norwegian industries improve the productivity of their work force, in terms of value added per working hour, there exists a declining trend in labor productivity of on-site construction Activities (Ahmad et al 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Figure 1: Labour productivity of on-site construction (Figure 15 in Ahmad et al, 2020) This defect stands out even more in the face of the new normal, due to the increase of TNC and Karunakaran et al (2019), indicate that it is more frequent in road works due to its longitudinal nature; however, the literature has been limited, for the most part, to address variability through none traditional tools in building construction. According to their research, the causes of variability in road works depend on factors that cause delays in the work flow.…”
Section: Introductionmentioning
confidence: 99%